การพัฒนาเซลล์การผลิตอัตโนมัติ : กรณีศึกษาเครื่องกัดซีเอ็นซีและหุ่นยนต์อุตสาหกรรม - ธเนศ รัตนวิไล (มหาวิทยาลัยสงขลานครินทร์, 2012)
A machining center, CINCINNATI, VMC 750 model and an industrial robot, KUKA, KR C6 model were formed a production cell to communicate and mutually work between two independent machines. An automated manufacturing cell development not only improves a production system to be more flexible but also increases an efficiency of each machine. The closed-open door and clamping system of machining center must be modified to operate by pneumatic system prior to connect both machines. The interface system for both machines to communicate can be subsequently applied by using M-function of the machining center. By creating the controlled program into the industrial robot and running the system, it was revealed that both machines can work together as a production cell. The result showed that both machines were accurately operated all steps of design process. The development of production cell between industrial robot and machining center was successfully achieved and able to develop more complicated flexible manufacturing systems.